Liposome sensing and monitoring by organic electrochemical transistors integrated in microfluidics - Tarabella, Giuseppe; Balducci, Anna Giulia; Coppedè, Nicola; Marasso, Simone; D'Angelo, Pasquale; Barbieri, Stefano; Cocuzza, Matteo; Colombo, Paolo; Sonvico, Fabio; Mosca, Roberto; Iannotta, Salvatore (Biochimica et biophysica acta, 2013)
Organic electrochemical transistors (OECTs), which are becoming more and more promising devices for applications in bioelectronics and nanomedicine, are proposed here as ideally suitable for sensing and real time monitoring of liposome-based structures. This is quite relevant since, currently, the techniques used to investigate liposomal structures, their stability in different environments as well as drug loading and delivery mechanisms, operate basically off-line and/or with pre-prepared sampling. OECTs, based on the PEDOT:PSS conductive polymer, have been employed as sensors of liposome-based nanoparticles in electrolyte solutions to assess sensitivity and monitoring capabilities based on ion-to-electron amplified transduction. We demonstrate that OECTs are very efficient, reliable and sensitive devices for detecting liposome-based nanoparticles on a wide dynamic range down to 10−5mg/ml (with a lowest detection limit, assessed in real-time monitoring, of 10−7mg/ml), thus matching the needs of typical drug loading/drug delivery conditions. They are hence particularly well suited for real-time monitoring of liposomes in solution. Furthermore, OECTs are shown to sense and discriminate successive injection of different liposomes, so that they could be good candidates in quality-control assays or in the pharmaceutical industry. Drug loading and delivery by liposome-based structures is a fast growing and very promising field that will strongly benefit from real-time, highly sensitive and low cost monitoring of their dynamics in different pharma and biomedical environments, with a particular reference to the pharmaceutical and production processes, where a major issue is monitoring and measuring the formation and concentration of liposomes and the relative drug load. The demonstrated ability to sense and monitor complex bio-structures, such as liposomes, paves the way for very promising developments in biosensing and nanomedicine. This article is part of a Special Issue entitled Organic Bioelectronics—Novel Applications in Biomedicine. ► Real-time sensing/monitoring liposomes by organic electrochemical transistor ► Very high sensitivity achieved for liposome-based nanoparticles sensing ► Demonstration of OECT being suitable for quality control assays ► Our studies pave the way for studying dynamics of drug-loading/delivery.